The Role of 68Ga-PSMA Positron Emission Tomography/Computerized Tomography for Preoperative Lymph Node Staging in Intermediate/High Risk Patients With Prostate Cancer: A Diagnostic Meta-Analysis - Tu, Xiang; Zhang, Chichen; Liu, Zhenhua; Shen, Guohua; Wu, Xiaoai; Nie, Ling; Chang, Tiancong; Xu, He; Bao, Yige; Yang, Lu; Wei, Qiang (Frontiers in Oncology, 2020)
Purpose To evaluate the accuracy of 68Ga-PSMA positron emission tomography/computerized tomography (PET/CT) for preoperative lymph node staging using histopathological results of pelvic lymph node dissection (PLND) as reference standard in patients with intermediate/high risk of prostate cancer. Material and methods A systematic search of PubMed, Embase, and the Cochrane Library was searched up to May, 2020. We included studies investigating accuracy of 68Ga-PSMA PET/CT in primary lymph node staging before radical prostatectomy and PLND. The pooled sensitivity, speciﬁcity, positive predictive value (PPV), negative predictive value (NPV), diagnostic odds ratio (DOR) and the summary receiver operating characteristic (SROC) curve with an area under the curve (AUC) were synthesized. Results Eleven studies comprising 904 patients were identified. Based on per-patient analysis, the pooled sensitivity and specificity reached 0.63 (95% CI: 0.46–0.78) and 0.93 (95% CI: 0.88–0.96) respectively, with the DOR of 22 (95% CI: 10-47). An overall accuracy was revealed by the SROC curve with AUC of 0.91 (95% CI: 0.88–0.93). Using the lymph node as unit, the pooled sensitivity and specificity were 0.70 (95% CI: 0.49-0.85) and 0.99 (95% CI: 0.96-1.00) respectively. And the DOR reached 167 (95% CI: 40-695) with an AUC of 0.96 (95% CI: 0.94-0.98). The pooled PPV and NPV all reached above 0.8 on basis of per-patient or per-node analysis. Conclusions 68Ga-PSMA PET/CT represented as a promising test for preoperative lymph node staging and patients without lymph node metastatic status can rarely be misdiagnosed. However, its sensitivity ought to be improved before forgoing PLND.